Stakeholder adoption of e-government services driving and resisting factors - Shareef, Mahmud Akhter 1966-; Gale Group (Hershey, Pa. Information Science Reference, 2011)
Examines the stakeholders of e-government and reveals the stages of growth or service maturity levels.
section 1. E-government development, adoption, and implementation : a global phenomenon. ch 1. Introduction to electronic government : development and adoption ; ch 2. An e-government strategic planning framework ; ch 3. Electronic government adoption paradigms -- section 2. Reformation of public administration : digitization of government. ch 4. Are cities in India digital yet? : some evidence ; ch 5. The roles of intermediaries in e-government diffusion and adoption : a case study of Madinah City in Saudi Arabia ; ch 6. The demand side for development of e-government services and gateway in Turkey : taking citizen perceptions and suggestions into account -- section 3. Adoption, proliferation, and resistance : growth of service maturity. ch 7. E-government adoption and proliferation across different stages of evolution ; ch 8. An empirical effort to validate electronic-government adoption model ; ch 9. Governing e-government (e-governance) : an operational framework -- section 4. Performance of e-government projects. ch 10. E-government development : performance evaluation parameters ; ch 11. A study of the implementation status of two e-governance projects in land revenue administration in India ; ch 12. Comparative study of e-government implementation in two public agencies in Oman.
Description based on print version record.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Internet in public administration; Electronic government information; Information technology -- Political aspects; Electronic books